FUNCTION OF THE SEKATEN GAMELAN IN THE SEKATEN CEREMONY - Anton Nugroho, Mukhlis (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
The Sekaten ceremony cannot take place without the presence of the Sekaten Gamelan. Two indispensable elements in the Sekaten event are the gamelan and the gunungan. However, this discussion focuses more on the Sekaten Gamelan, which is played every day during the Sekaten ceremony. This fact has prompted researchers to delve deeper into how the gamelan is utilized in the Sekaten ceremony. This research employs a qualitative approach that combines literature review, interviews, and field observations to gain a profound understanding of the function of the Sekaten Gamelan in the Sekaten ceremony. Through the analysis of practices conducted by the king, the courtiers, and the attending community during the Sekaten ceremony, it can be seen that the Sekaten Gamelan holds a special position and serves several functions. The analysis of the functions of the Sekaten Gamelan reveals at least four functions: as a tool to demonstrate the king's existence, as a means to gather the masses, as a marker for the beginning of the Sekaten ceremony, and as a medium for religious preaching to recall Islamic teachings.